Land use change trajectories, conservation status and social importance of dry forests in Nicaragua. (27th May 2014) - RAVERA, FEDERICA; TARRASÓN, DAVID; ESPELTA, JOSEP MARÍA
SUMMARY: Interdisciplinary studies have proved the interconnectedness of history and ecology relevant to forest conservation proposals and management policies. Engaging local views and concerns in the evaluation and monitoring process can lead to more robust knowledge in the pursuit of effective conservation. This study aimed to assess the degree to which land use change trajectories influence the state of tropical dry forest conservation, as evaluated by scientists and local people. Focusing on northern Nicaragua, the research identified three historical trajectories for types and magnitude of forest disturbance. The assessment process included inventorying sites under different trajectories and integrating ecological and social indicators (namely local perceptions of biodiversity value and concern over species threat). The different land use change trajectories had no influence on the present structure of the dry forest, but strongly affected species diversity, composition and their social importance. The study provided evidence of positive species selection by farmers, which suggested a feedback loop between ecological conditions, social value and awareness of conservation.